Wear analysis research on railway steel - To, Jason Wei Lin (2019)
Sliding wear often occurs at the side of the rail head, especially when the trains are making sharp turns. Sliding wear on rail and wheel is known to cause more wear as compared to rolling and rolling-sliding wear. It can become very costly if the operator fails to predict wear effectively. If a wear model simulation can be achieved, operators can better schedule and prepare for periodic checks, which can help save time and money. In order to conduct sliding wear analysis of rail, it must first be broken down into a few parts: geometrical component, tangential component and normal component. Due to the complexity of the wheel and rail profile, a pin-on-disc model is often used to conduct sliding wear test as it is lab-friendly, simple and versatile. This report presents the experimental and FEA method to conduct ball-on-disc experiment. For the experimental ball-on-disc setup, the ball is fixed to a support with a constant angular velocity rotating disc and a constant load acting on the ball. The wear volume is calculated using a stylus profilometer. For the FEA of the pin-on-disc setup, the model is replicated based on the experimental ball-on-disc setup using a FEA software, ABAQUS. The 2D and 3D contact problem is modelled and solved, which is a prerequisite wear analysis. The 2D and 3D model results for the ball-on-disc simulation are validated by comparing the contact pressure based on FEM and Hertzian Contact Theory.